EKSPERYMENTALNA GLOTTODYDAKTYKA OKULOGRAFICZNA NA PRZYKŁADZIE BADAŃ WŁASNYCH - Andrychowicz-Trojanowska, Agnieszka (Neofilolog, 2018)
The aim of this paper is to present a possible technological support for glottodidactic research. To do this the author shortly characterises eyetracking in relation to the humanities, especially glottodidactics. She introduces and describes the idea of experimental eyetracking glottodidactics on the basis of her own eyetracking research for EFL textbooks, and presents the basic results of the research and general conclusions.